STRATEGI DUAL-CURRICULUM DALAM IMPLEMENTASI PENDIDIKAN MULTIDISIPLIN DI PONDOK PESANTREN MODERN - Ali Masdar Fahim; Agus Nuril Anwar; Ahmad Sirojul Mabrur; Muhammad Umar Faruq; Muhammad Adib (Jurnal Al-Fatih, 2025)
Religious education (Salaf) and modern science are two contrasting elements that generate graduates who are either religiously competent yet retrograde in terms of technology, or the reverse. Conversely, this research aims to explore and examine the application of the multidisciplinary approach at Pondok Pesantren Modern Al-Rifa’ie 3 Malang, specifically how the creating body manages its continuity within traditional frameworks, known as "Kitab Kuning," and how it incorporates modern subject matter into its methodology and approach. Applying the research method as a case analysis, the researcher shall gather information through in-depth interviews and observation. The research reveals that the concept of "multidisciplinary" at Al-Rifa’ie 3 is implemented within a Dual-Track System (Separated Curriculum) framework. Originally, the system at Al-Rifaie 3 applied an entirely integrated approach (including the system), which unfortunately had been ceased due to time and human resources issues. Recently, the approach has been functionally and partially integrated via the Bahtsul Masail Institute (LBM) and specialized extracurricular activities (Jam'iyyah) and not through classroom teaching. Besides, several challenges are also ascertainable, among which are the pragmatism among parents who place greater emphasis on recognized diplomas than religious capability, and lack of time management among the graduates. Based on these concerns and research findings, this research concludes that the modernization at Al-Rifaie 3 is that of its management and teaching approach and is far from diminishing the elements at its Salaf and is nothing more than an approach that is very realistic and feasible and serves as an effective strategy that produces more competitive graduates who are well-attuned in science and technology yet very loyal and proud of its strong adherence and identity as an Islamist movement.